2019
DOI: 10.1017/s004388711800031x
|View full text |Cite
|
Sign up to set email alerts
|

Naming and Praising in Humanitarian Norm Development

Abstract: To examine the early development of humanitarian norm cascades, the author focuses on the processes that led to the adoption of the 1997 Mine Ban Treaty and the 2008 Convention on Cluster Munitions. Even though major military powers like the United States, Russia, and China opposed these initiatives, the latter set in motion quick norm cascades that brought about international legal norms stigmatizing land mines and cluster munitions. It is conventionally asserted that international norms emerge either due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…As illustrated in Chapter 5, on social media, third sector actors are norm leaders, or norm entrepreneurs. They use tactics like "altercasting" to project roles onto the targets of their normative campaigns (Petrova, 2019), or use the reverse panda effect I described in Chapter 5 to evoke outrage among their audiences that is directed at a particular target. In the Nestle Waters case study, this was a deliberate framing exercise that was designed to sway public opinion and societal norms concerning water taking by water bottling companies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As illustrated in Chapter 5, on social media, third sector actors are norm leaders, or norm entrepreneurs. They use tactics like "altercasting" to project roles onto the targets of their normative campaigns (Petrova, 2019), or use the reverse panda effect I described in Chapter 5 to evoke outrage among their audiences that is directed at a particular target. In the Nestle Waters case study, this was a deliberate framing exercise that was designed to sway public opinion and societal norms concerning water taking by water bottling companies.…”
Section: Discussionmentioning
confidence: 99%
“…As Finnemore and Sikkink, Sunstein (1996), and others (e.g., Petrova, 2019) have noted, like most behavioural phenomena grounded in emotion, normative processes are notoriously difficult to quantify. Sunstein (1996) has observed that "many important and well-known anomalies in human behavior are best explained by reference to social norms and to the fact that people feel shame when they violate those norms."…”
Section: Characterizing Norm Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on regime shifting (Helfer 2004), contested multilateralism (Morse and Keohane 2014), and regime complexity (Alter and Meunier 2009;Alter and Raustiala 2018) suggests a course of action permitting strengthening the disarmament regime through the TPNW despite possible nuclear weapon states' opposition. Ironically, this initial nuclear weapon state opposition to the TPNW over time may serve to strengthen both the treaty and the disarmament regime (Petrova 2019). This involves TPNW member states creating new institutional elements to develop, advance and entrench treaty goals, policies and practices, which would complement existing instruments and structures, encourage innovation, and increase the likelihood of identifying possible implementation and verification challenges and finding solutions by the time they may be needed.…”
Section: Introductionmentioning
confidence: 99%
“…Alcade, 2014;Bolton and Nash, 2010;Bower, 2015;Garcia, 2015;Price, 1998;Rutherford, 2000Rutherford, , 2011. Some studies belonging to this literature also uncover additional and more specific aspects of these normative changes (Petrova, 2019;Rosert, 2019aRosert, , 2019b. Overall, the constructivist research on ICW treaties offers a compelling explanation for the creation of these treaties, as well as for the changes in the practices of states related to ICWs, and yet the global socialization processes cannot satisfactorily account for the variation among states in ratification of the ICW treaties.…”
mentioning
confidence: 99%